Cerebral blood flow regulation is not acutely altered after a typical number of headers in women footballers - Jack, Jacob; Woodgates, Alex; Smail, Oliver; Brown, Felix; Lynam, Katie; Lester, Alice; Williams, Genevieve; Bond, Bert (Frontiers in Neurology, 2022)
Background The repeated act of heading has been implicated in the link between football participation and risk of neurodegenerative disease, and acutely alters cerebrovascular outcomes in men. This study assessed whether exposure to a realistic number of headers acutely influences indices of cerebral blood flow regulation in female footballers. Methods Nineteen female players completed a heading trial and seated control trial on two separate days. The heading trial involved six headers in 1 h (one every 10 min), with the ball traveling at 40 ± 5 km/h. Cerebrovascular reactivity to hypercapnia and hypocapnia was determined using serial breath holding and hyperventilation attempts. Dynamic cerebral autoregulation (dCA) was assessed by scrutinizing the relationship between cerebral blood flow and mean arterial blood pressure during 5 min of squat stand maneuvers at 0.05 Hz. Neurovascular coupling (NVC) was quantified as the posterior cerebral artery blood velocity response to a visual search task. These outcomes were assessed before and 1 h after the heading or control trial. Results No significant time by trial interaction was present for the hypercapnic (P = 0.48, ηp2 = 0.05) and hypocapnic (P = 0.47, ηp2 = 0.06) challenge. Similarly, no significant interaction effect was present for any metric of dCA (P > 0.12, ηp2 < 0.16 for all) or NVC (P > 0.14, ηp2 < 0.15 for all). Conclusion The cerebral blood flow response to changes in carbon dioxide, blood pressure and a visual search task were not altered following six headers in female footballers. Further study is needed to observe whether changes are apparent after more prolonged exposure.